Language of mothers and fathers in interaction with their autistic children - Perzolli, Silvia; Bentenuto, Arianna; de Falco, Simona; Venuti, Paola (Frontiers in Psychiatry, 2023)
Introduction Verbal language is one of the most immediate and significant means parents have to express affect and information to their children. Parental speech directed to children has been thoroughly examined in typical development. However, the characteristics of parental speech directed to children with neurodevelopmental disorders are far less well documented, and no recent studies have been carried out that involve autistic1 children and their fathers. Therefore, the present study aims to analyze and compare maternal and paternal speech directed to young autistic children, focusing on fathers’ elements of speech in comparison with maternal language. Methods N = 88 dyads participated in this study. 44 autistic children (41 males and 3 females) (chronological age: M = 40.01 months; SD = 11.96) in interaction with their fathers (paternal age M = 41.84 years; SD = 7.02) and the same 44 children in interaction with their mothers (maternal age M = 37.37 years; SD = 5.45). The language was verbatim transcribed using ELAN software (ELAN Version 6.4, 2022) and coded with an observational tool (Penman) for analyzing functions and referents of speech after reaching a satisfactory level of agreement between two independent transcribers. Results No differences emerged considering the affective aspects of speech. However, mothers seem to direct more informative salient statements (W = 1,259; p = 0.02) and call the child’s attention more often than fathers (W = 1,253.5; p = 0.02). Regarding referents of informative speech, fathers focused more on the child’s internal states rather than mothers (W = 727; p = 0.04). Discussion These results reveal that fathers seem to display a relationship-based approach focused on a non-intrusive style with few demands while talking with their children, providing a complementary role to mothers that allows complete and harmonious stimulation of all areas of child development.